Fundamentals and applications in aerosol spectroscopy - Signorell, Ruth (CRC Press, 2011)
"Helping you better understand the processes, instruments, and methods of aerosol spectroscopy, fundamentals and applications in aerosol spectroscopy provides an overview of the state of the art in this rapidly developing field. It covers fundamental aspects of aerosol spectroscopy, applications to atmospherically and astronomically relevant problems, and several aspects that need further research and development.Chapters in the book are arranged in order of decreasing wavelength of the light/electrons. The text starts with infrared spectroscopy, one of the most important aerosol characterization methods for laboratory studies, field measurements, remote sensing, and space missions. It then focuses on Raman spectroscopy for investigating aerosol processes in controlled laboratory studies and for analyzing environmental particles and atmospheric pollution. The next section discusses the use of cavity ring-down spectroscopy to measure light extinction, laser-induced fluorescence spectroscopy to identify and classify biological aerosol particles, and ultrafast laser techniques to improve the specificity of bioaerosol detection. The final section examines recent developments involving novel techniques based on UV, X-ray, and electron beam studies.This book offers the first comprehensive overview of the spectroscopy of aerosols. It includes some results for the first time in the literature and presents a unique link between fundamental aspects and applications"--
Formerly CIP Uk. - Includes bibliographical references and index
Keywords: Aerosol; Optische Spektroskopie